2013
DOI: 10.1002/cphc.201300558
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Metal⋅⋅⋅π Interactions and Hydrogen Bonds: Some Unusual Synergetic Effects of Coinage Metals and Substituents

Abstract: The ternary systems of C(2)H(4) (C(2)H(2) or C(6)H(6))-MCN-HF (M=Cu, Ag, Au) and the respective binary systems were investigated to study the interplay between metal⋅⋅⋅π interactions and hydrogen bonds. The metal⋅⋅⋅π interactions in C(2)H(4)-MCN become stronger with the irregular order Ag Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 49 publications
(42 reference statements)
1
14
0
Order By: Relevance
“…The total interaction energy ranges from −43.81 kcal/mol in C 2 H 2 −AgCN−XeF 2 O to −68.44 kcal/mol in C 2 H 4 −AuCN−XeF 2 O (Table 5), and it has a consistent change with the regium bonding interaction energy since the regium bond is much stronger than the aerogen bond. C 2 H 4 is a better electron donor to form a regium bond with AgCN and AuCN than C 2 H 2 , while an opposite result is found for CuCN due to the larger distortion of C 2 H 2 when it binds with CuCN [52] . The total interaction energy of MCN−C 2 H 4 −XeF 2 O is smaller 11 kcal/mol than that of C 2 H 4 −MCN−XeF 2 O.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…The total interaction energy ranges from −43.81 kcal/mol in C 2 H 2 −AgCN−XeF 2 O to −68.44 kcal/mol in C 2 H 4 −AuCN−XeF 2 O (Table 5), and it has a consistent change with the regium bonding interaction energy since the regium bond is much stronger than the aerogen bond. C 2 H 4 is a better electron donor to form a regium bond with AgCN and AuCN than C 2 H 2 , while an opposite result is found for CuCN due to the larger distortion of C 2 H 2 when it binds with CuCN [52] . The total interaction energy of MCN−C 2 H 4 −XeF 2 O is smaller 11 kcal/mol than that of C 2 H 4 −MCN−XeF 2 O.…”
Section: Resultsmentioning
confidence: 89%
“…In this manuscript, we studied the binary complexes of C 2 H 2 −MCN, C 2 H 4 −MCN, C 2 (CN) 4 −MCN, C 2 H 4 −XeF 2 O, and MCN−XeF 2 O, in which M is a coinage metal atom including Cu, Ag, Au. The C 2 H 2 −MCN, C 2 H 4 −MCN, and C 2 (CN) 4 −MCN complexes have been studied in the previous studies [51–54] . By comparing with HCN−XeF 2 O, we can unveil the M substitution effect on the strength of coinage‐metal bond.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…We are also interested in comparing different types of non‐covalent interactions involving MCN. It was found that MCN engages in a hydrogen bond with HF, a halogen bond with ClF, and a tetrel bond with SiF 4 . Moreover, the corresponding interaction is stronger from SiF 4 to ClF to HF to ZX 3 (Z = B, Al; X = H, F).…”
Section: Resultsmentioning
confidence: 92%
“…Furthermore, using atoms in molecules (AIM) and natural bond orbital (NBO) methods, the nature of the complexes between H 2 O and H 2 S acting as the Lewis basis and AuCl as a Lewis acid was characterized [38], and the intermolecular interaction between phosphines (XH 2 P with X = H, CH 3 , F, CN and NO 2 ) and MY molecules (M = Cu, Ag, Au and Y = F, Cl, Br and I) [39]. Cooperativity in ternary complexes involving the regium bond was also explored [40][41][42][43]. The properties of complexes of Au(I) and Au(III) were compared using the CCSD(T)/CBS computational level [44].…”
Section: Introductionmentioning
confidence: 99%